The role of student’s awareness of current experiences on peer and emotional problems and school refusal - Sorrenti, Luana; Meduri, Carmelo Francesco; Caparello, Concettina; Fumia, Angelo; Filippello, Pina (Frontiers in Psychology, 2025)
IntroductionSeveral studies have shown that awareness of present experiences/events can play a key role in promoting relational and emotional well-being as well as motivation to attend school. However, no study to date has analyzed whether a student’s awareness of current experiences (mindfulness) may contribute to peer and emotional problems and thus promote or reduce school refusal (Anxious Anticipation, Difficult Transition, Interpersonal Discomfort and School Avoidance).MethodsA cross-sectional study (362 Italian high school students) was conducted to evaluate the mediating role of peer problems and emotional problems in the association between students’ awareness of their current experiences (mindfulness) and school refusal. In order to evaluate the association between variables, was to carry out a structural equation model (SEM) with latent variables [χ2(188) = 372.163, p = 0.000, CFI = 0.94, SRMR = 0.04, RMSEA (90%CI) = 0.052 (0.044, 0.060)].ResultsMediation analysis indicated that peer problems and emotional problems full mediate the association between mindfulness and Anxious Anticipation (peer problems: β_= −0.19, p = ≤0.001; emotional problems: β_= −10,p = ≤0.05) and Interpersonal Discomfort (peer problems: β_= −0.35, p = ≤0.001; emotional problems: β_= −0.14, p = ≤0.01). Moreover, peer problems fully mediate the association between mindfulness and School Avoidance (β_= −0.14, p = ≤0.01).DiscussionThe study extends knowledge of the factors involved in school refusal, with application implications from a preventive point of view, relating to the components of emotional, relational and current experience awareness that may be related to motivation to attend school.